2005
DOI: 10.1118/1.2011089
|View full text |Cite
|
Sign up to set email alerts
|

Energy modulated electron therapy using a few leaf electron collimator in combination with IMRT and 3D‐CRT: Monte Carlo‐based planning and dosimetric evaluation

Abstract: Energy modulated electron therapy (EMET) based on Monte Carlo dose calculation is a promising technique that enhances the treatment planning and delivery of superficially located tumors. This study investigated the application of EMET using a novel few-leaf electron collimator (FLEC) in head and neck and breast sites in comparison with three-dimensional conventional radiation therapy (3D-CRT) and intensity modulated radiation therapy (IMRT) techniques. Treatment planning was performed for two parotid cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…The latchbit modification software ͑written in C code͒ converts the 23 independent latch bit tags into one single 23 bit binary number. The number of beamlets that a phase space can be divided into has now increased from 23 to 2 23 . The open-field phase space is converted into n individual phase space files-one per beamlet.…”
Section: Segmentation Of Beamlets From Phase Spacementioning
confidence: 99%
See 1 more Smart Citation
“…The latchbit modification software ͑written in C code͒ converts the 23 independent latch bit tags into one single 23 bit binary number. The number of beamlets that a phase space can be divided into has now increased from 23 to 2 23 . The open-field phase space is converted into n individual phase space files-one per beamlet.…”
Section: Segmentation Of Beamlets From Phase Spacementioning
confidence: 99%
“…Al-Yahya et al calculate predefined geometric "fieldlet" doses using Monte Carlo data and optimize the fieldlet selection and electron energy ͑EMRT-energy modulated radiation therapy͒. 23 The technique proposed in this paper implements a novel method for segmenting a uniform phase space output from a BEAMnrc linear accelerator simulation into individual phase space beamlets. 24 These individual beamlets of phase space are projected onto a patient-specific phantom and the dose deposition distribution is simulated using DOSXYZnrc.…”
Section: Introductionmentioning
confidence: 99%
“…The DoF have also been extended for electron therapy, for example, modulated electron radiotherapy (MERT) [14][15][16][17][18][19][20][21][22] combines intensity and energy modulation. The typically available electron beam energies of 6-22 MeV offer a large variety of different particle ranges.…”
Section: Introductionmentioning
confidence: 99%
“…15 The efficacy of MERT in combination with 3D-CRT and IMRT was tested with results showing reduced whole body dose over the photon modalities alone. 16 Gauer et al 17 have showed superior MERT plans of whole breast and chest wall irradiations when compared to helical photon IMRT, while Salguero et al 18 showed MERT to be superior to conventional electrons for postmastectomy chest wall irradiations.…”
Section: Introductionmentioning
confidence: 99%